Skills of management - Rees, W. David; Porter, Christine (South-Western Cengage Learning, 2008)
Starting with the transition to a managerial role, this book deals with management skills. They are discussed alongside the key themes of time management and the need for identification of objectives and diagnosis of problems before action.